Emulsion, hydrogel and emulgel systems and novel applications in cannabinoid delivery: a review. Issue 29 (17th October 2022) - Light, Kelly; Karboune, Salwa
Abstract: Emulsions, hydrogels and emulgels have attracted a high interest as tools for the delivery of poorly soluble hydrophobic nutraceuticals by enhancing their stability and bioavailability. This review provides an overview of these delivery systems, their unique qualities and their interactions with the human gastrointestinal system. The modulation of the various delivery systems to enhance the bioavailability and modify the release profile of bioactive encapsulates is highlighted. The application of the delivery systems in the delivery of cannabinoids is also discussed. With the recent increase of cannabis legalization across North America, there is much interest in developing cannabis edibles which can provide a consistent dose of cannabinoids per portion with a rapid time of onset. Indeed, the long time of onset of psychoactive effects and varied metabolic responses to these products result in a high risk of severe intoxication due to overconsumption. Sophisticated emulsion or hydrogel-based delivery systems are one potential tool to achieve this goal. To date, there is a lack of evidence linking specific classes of delivery systems with their pharmacokinetic profiles in humans. More research is needed to directly compare different classes of delivery systems for the gastrointestinal delivery of cannabinoids.